Efficacy of Nutrient Management Options for Finger Millet Production on Degraded Smallholder Farms in Eastern Uganda - Ebanyat, Peter; de Ridder, Nico; Bekunda, Mateete; Delve, Robert J.; Giller, Ken E. (Frontiers in Sustainable Food Systems, 2021)
Poor soil fertility is a major problem constraining crop productivity in smallholder farms of sub-Saharan Africa due to inadequate replenishment of nutrients removed. Nutrient additions are required to increase crop production on degraded fields. We use experimental data for three seasons to evaluate the potential of inorganic fertilisers and organic manures to offset finger millet yield differences or gap between degraded fields and former kraals, which are recognised as niches for obtaining the best yields within the Teso farming system in Eastern Uganda. N, P fertilisers were sole applied at 0, 30, 60, 90 kg ha–1 and in combination (N+P) at equal rates of sole application, and manure (3 t ha–1) supplemented with N (0, 30, 60 and 90 kg ha–1) to degraded fields located in upper and middle landscape positions in Chelekura and Onamudian villages. A second control treatment of millet grown on soils of former kraal sites (high fertility niches) was included as a benchmark to evaluate the efficacy of nutrient management options on degraded field. Average grain yield ranged from 404 kg ha–1 to 2026 kg ha–1 and differed significantly (P<0.001) between villages and seasons. Significant effects (P<0.05) of landscape position on grain yield were observed only in Onamudian village. Although the treatments significantly increased millet yields on degraded fields above the control, they could not eliminate the yield differences between degraded fields and former kraals. The largest average grain yields on degraded fields were obtained from combined application of N+P resulting in average grain yields of 800 kg ha–1 and 1171 kg ha–1 in in Chelekura village and Onamudian village respectively. These yield responses resulted in only 24% and 43% of yields obtained on former kraal fields in Chelekura and Onamudian respectively. The were low; often less than 25%. Pot experiments showed that S and K were additional limiting nutrients to N and P for f in Chelekuka and Onamudian and may partly explain the large yield differences of finger millet between fertilized fields and former kraals. Nutrient management strategies for sustainable millet production in these farming systems need consideration of site-specific nutrient limitations.